1990
DOI: 10.1111/j.1600-079x.1990.tb00808.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Melatonin Administration and Long Day‐Length on Endocrine Cycles in the Hedgehog Erinaceus europaeus

Abstract: The effects of exogenous melatonin (subcutaneous implants containing 0.031 +/- 0.006 mg/gm body mass melatonin) or long photoperiod (18L:6D) on wild-caught adult male hedgehogs were studied. Hedgehogs were implanted with melatonin-filled or empty capsules in May, August, or September, or maintained under long photoperiod from August. Blood samples collected at monthly intervals were assayed for testosterone, melatonin, and thyroxin. Melatonin-filled capsules elevated plasma melatonin concentrations for 4-6 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The results of the present study also supports an earlier finding in the Syrian hamster that suggests it is not the cessation of melatonin secretion by the pineal gland but rather a refractoriness of melatonin that results in the initiation of gonadal recrudescence in the spring time [Brainard et al, 19831. Further, other evidence suggest that the sensitivity to the antigonadal activity of melatonin is greatly influenced by season and photothermal conditions [Pevet et al, 1989;Fowler and Racey, 1990;Forsberg and Madej, 19901. Thus, the decline in testicular activity during winter dormancy in S. heathi could be because of increased testicular sensitivity to the melatonin signal as compared with other stages of the reproductive cycle.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present study also supports an earlier finding in the Syrian hamster that suggests it is not the cessation of melatonin secretion by the pineal gland but rather a refractoriness of melatonin that results in the initiation of gonadal recrudescence in the spring time [Brainard et al, 19831. Further, other evidence suggest that the sensitivity to the antigonadal activity of melatonin is greatly influenced by season and photothermal conditions [Pevet et al, 1989;Fowler and Racey, 1990;Forsberg and Madej, 19901. Thus, the decline in testicular activity during winter dormancy in S. heathi could be because of increased testicular sensitivity to the melatonin signal as compared with other stages of the reproductive cycle.…”
Section: Discussionmentioning
confidence: 99%
“…A significantly elevated progesterone level was observed during active fetal development accompanied by placental growth reaching a peak prior to parturition [24]. Fowler and Racey [26] demonstrated that elevated melatonin level is important in the regulation of endogenous hormonal cycle in hedgehog during winter. The studies on rodents showed inhibitory effect of melatonin on ovarian function [27,28].…”
Section: Introductionmentioning
confidence: 99%